Utilização de resíduos de rochas ornamentais na fabricação de vidros sodo-cálcicos - Bastos, Isadora Andrade (2018)
The processing of dimension stones generated, in 2018, 3,260,000 tons of waste in Brazil. The solid waste generated in the processing of these stones presents a high recyclability potential as a raw material for glassmaking, due to the presence of some oxides in its composition as Na2O, o MgO, o CaO, o K2O, o Al2O3, and SiO2, the main oxide that forms the vitreous network and the most abundant in granites and quartzites. Thus, the primary goal of this paper was to evaluate the technical viability of soda-lime glass production using dimensional stone residues, at a temperature of 1200 °C, without the use of sand. Also, to perform the physical-chemical characterization of the raw materials used: sludge from the processing of dimension stones (LBRO) heterogeneous - from different types of stones and companies -, and quartzite residue; producing soda-lime glass varieties with the dimension stone wastes; and perform the physico-chemical characterization of the glasses produced. The results of the x-ray diffraction (XRD) on the produced glass evidenced its complete vitrification. The x-ray fluorescence analysis (XRF) provided the chemical composition of the glasses and proved characteristics similar to the standard evidenced in conventional soda-lime glasses. The values of density of the glasses obtained were 2.48 g/cm3 , 2.62 g/cm3 , 2.67 g/cm3 and 2.71 g/cm3 , all close to the nominal density of sodalime glasses, 2.5 g/cm3 . The hydrolytic resistance of the glasses was classified as very low (HGB 5) in all samples according to ISO 719. The compositions produced with LBRO resulted in amber glasses due to the combination of sulfur oxide and iron oxide present in and in green glasses, due to the presence of high iron content in the sample, while glass produced with quartzite, without LBRO, resulted in colorless glasses. It was concluded that there is technical feasibility in the production of soda-lime glasses with the use of ornamental rock residues at low temperature (1200 ° C) and without the addition of sand, and that these residues have potential for effective large-scale employment.